Mesenchymal Stem Cell Treatment for Steroid Refractory Graft-versus-Host Disease in Children: A Pilot and First Study from Turkey. (13th December 2015) - Erbey, Fatih; Atay, Didem; Akcay, Arzu; Ovali, Ercument; Ozturk, Gulyuz
Abstract : This study evaluated the efficacy of mesenchymal stem cells (MSCs) from bone marrow of a third-party donor for refractory aGVHD. We report the first experience using MSCs to treat refractory aGVHD in 33 pediatric patients undergoing allogeneic HSCT from Turkey. Totally, 68 doses of bone marrow derived MSCs were infused. The median dose of MSC was1.18 × 10 6 cells per kg body weight. Overall, complete response (CR) was documented in 18 patients, partial response (PR) was documented in 7 patients, and no response (NR) was documented in 8 patients. The 2-year estimated probability of overall survival (OS) for patients achieving CR and PR/NR was 63.8% and 29.4%, respectivelyp = 0.0002 . While the cumulative incidence of transplant related mortality (TRM) at day 100 after first MSC infusion was 46.6% in PR/NR patients, there was no any TRM at day 100 after first MSC infusion in CR patientsp = 0.001 . Twelve patients developed chronic GVHD (cGVHD); eight of them were alive, with five having extensive disease and three having limited disease. In conclusion, MSCs appear to be safe and effective treatment option for pediatric patients with steroid refractory aGVHD. But the efficacy of MSCs on cGVHD in aGVHD patients treated with MSCs seems to be limited.